The Influence of Organizational Culture and Leadership Style on Motivation and its Impact on Employee Performance - MS, M Zahari; Akbar, Ali; Nuraini, Siti (Ekonomis: Journal of Economics and Business, 2025)
Learning more about workplace motivation, leadership style, corporate culture, and employee performance is the aim of this study. It also seeks to examine how leadership style and organizational culture affect employee performance and motivation at work, both directly and indirectly. Lastly, it looks at how employee performance is affected by workplace motivation. Conducted at the Office of Subdistrict Head Tungkal Ilir in West Tanjung Jabung Regency, There were 48 employees in the study's sample. Using census sampling methods, all personnel served as subjects for the investigation. Descriptive statistical analysis revealed that both organizational culture and leadership style were categorized as good, whereas employee motivation and performance were classified as high. Through path analysis, It was discovered that leadership style and organizational culture exert both direct and indirect influences over employee motivation and performance. Moreover, simultaneous and partial tests confirmed that there is a statistically significant positive correlation between organizational culture, leadership style, motivation levels, and overall employee performance. In summary, improved organizational culture coupled with suitable leadership practices contribute positively to higher employee motivation. Consequently, motivated staff perform optimally in delivering superior work outputs for the organization.